2016
DOI: 10.1039/c5mb00698h
|View full text |Cite
|
Sign up to set email alerts
|

Lysyl oxidase promotes epithelial-to-mesenchymal transition during paraquat-induced pulmonary fibrosis

Abstract: Lysyl oxidase (LOX) is a copper-dependent amine oxidase that plays a critical role in pulmonary fibrosis. Our previous study demonstrated that epithelial-to-mesenchymal transition (EMT) was strongly associated with paraquat (PQ) induced pulmonary fibrosis. This present study was aimed to evaluate the potential involvement of LOX on EMT in the process of pulmonary fibrosis induced by PQ. We established an in vivo rat model and an in vitro cell model induced by PQ treatment and found that LOX protein expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 32 publications
5
20
0
Order By: Relevance
“…LOX participates in various fibrosis processes, such as lung, myocardial and renal fibrosis ( 16 18 ). As demonstrated in a previous study by the present authors, LOX promotes EMT in PQ-induced PF ( 8 ). LOX was previously considered a critical target of HIF-1α ( 19 ); however, HIF-1α and LOX have since been demonstrated to provide bidirectional regulation of colon and ovarian carcinomas ( 20 , 21 ).…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…LOX participates in various fibrosis processes, such as lung, myocardial and renal fibrosis ( 16 18 ). As demonstrated in a previous study by the present authors, LOX promotes EMT in PQ-induced PF ( 8 ). LOX was previously considered a critical target of HIF-1α ( 19 ); however, HIF-1α and LOX have since been demonstrated to provide bidirectional regulation of colon and ovarian carcinomas ( 20 , 21 ).…”
Section: Introductionsupporting
confidence: 87%
“…Alveolar epithelial cells could acquire mesenchyme cell phenotypes through EMT, these cells could then increase the deposition of extracellular matrix and further promote the development of PF ( 5 7 ). Furthermore, EMT has been demonstrated to serve an important role in PQ-induced PF in recent studies by the present authors ( 8 , 9 ).…”
Section: Introductionsupporting
confidence: 56%
“…We found that a lysyl oxidase 1 (LOX1) homologue in Botryllus is highly expressed during the entire asexual cycle and hypothesized that it could play a role in vascular homeostasis ( Figure 1B ). In vertebrates, LOX1 is secreted by a number of tissues, including blood vessels, and plays a critical role in modifying the basement membrane by cross-linking collagen and elastin, thus controlling the stiffness of the ECM ( Bignon et al , 2011 ; Chen et al , 2013 , 2015 ; Cox et al , 2015 ; Liu et al , 2015 ; Wang et al , 2016 ). Disruption of LOX activity can affect multiple tissues, including blood vessels, lungs, bone, and ligaments, and can increase the risk of aortic aneurysms ( Smith-Mungo and Kagan, 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, if BAPN appears to not inhibit a LOX isoform in vivo, then it is likely that (1) either BAPN has been metabolized, or (2) that the activity in question occurs as a result of a non-enzymatic function of LOX or LOX isoform. Data consistently show LOX up-regulated in a variety of fibrotic conditions, sometimes accompanied by additional LOX isoforms, including lung- 49-53 , liver- 43, 54-56 , and heart- 57, 58 , and skin- 59-61 fibrosis, and hypertension 47, 58 . One notable exception is phenytoin-induced gingival overgrowth which appears to be accompanied by LOXL2 elevations and not LOX 62, 63 .…”
Section: Bodymentioning
confidence: 90%